ASSESSMENT OF THE EUROPEAN UNION STRUCTURAL ASSISTANCE AUDIT MODEL - Lakis, Vaclovas; Simonaitytė, Živilė (Ekonomika, 2011)
The paper covers an analysis and critical assessment of the procedure of selecting the audit model for the European Union structural assistance and elaborates on applicable models. It reviews the authorities of the EU Member States tasked with the performance of the auditing function. The article provides an assessment of the status of the supreme audit institution which acts as a body auditing structural assistance. The conclusion is drawn that in cases when the provisions of different auditing standards differ, regulations of the European Union should specify the particular requirements applicable to the audit.